Developing a taxonomy to characterise trusted adult support in the lives of adolescents. (20th August 2019) - Pringle, Jan; McAteer, John; Whitehead, Ross; Scott, Eileen; Milne, Dona; Jepson, Ruth
ABSTRACT: Introduction: A systematic review of trusted adult interventions for adolescents revealed that there was no common terminology, agreed explicit definition, or detail, regarding the personal qualities, functions and roles fulfilled by trusted adults that was used consistently across the papers. To provide clarity, we therefore aimed to produce a taxonomy of trusted adult input, using evidence drawn from our review. Methods: Data from the review findings were used to compile the taxonomy, moving from the general to the more specific, in a four stage process. This involved: (1) compilation of elements described in individual papers, (2) grouping of elements derived from stage 1 into categories, (3) examination of context and nature of the relationship, (4) development of a categorisation of trusted adult input. Findings: The resulting taxonomy encapsulates core essential qualities provided by people acting in trusted adult or mentoring roles, and gives details relating to what a young person might expect from individuals they put their trust in. The taxonomy consists of six categories relating to: delivery context, roles of trusted adults, nature of support, personal qualities, actions/functions, and impact. Conclusions: The taxonomy describes key elements that define the trusted adult role, and has the potential to inform the development of policies and guidelines relating to support provision. It may be used as a framework for the reporting of trusted adult interventions within research, and act as a helpful guide if a young person is in doubt about the behaviour or qualities displayed by an adult in their environment.